Digital communication receivers synchronization, channel estimation, and signal processing - Meyr, Heinrich (Wiley series in telecommunications and signal processing, 1997)
Digital Communication Receivers offers a complete treatment on the theoretical and practical aspects of synchronization and channel estimation from the standpoint of digital signal processing. The focus on these increasingly important topics, the systematic approach to algorithm development, and the linked algorithm-architecture methodology in digital receiver design are unique features of this book.